Transplanting Intact Donor Tissue Enhances Dopamine Cell Survival and the Predictability of Motor Improvements in a Rat Model of Parkinson’s Disease - Fricker, Rosemary A.; Kuiper, Jan Herman; Gates, Monte A. (PLOS ONE, 2012)
Primary cell transplantation is currently the gold standard for cell replacement in Parkinson’s disease. However, the number of donors needed to treat a single patient is high, and the functional outcome is sometimes variable. The present work explores the possibility of enhancing the viability and/or functionality of small amounts of ventral mesencephalic (VM) donor tissue by reducing its perturbation during preparation and implantation. Briefly, unilaterally lesioned rats received either: (1) an intact piece of half an embryonic day 13 (E13) rat VM; (2) dissociated cells from half an E13 rat VM; or (3) no transplant. D-amphetamine- induced rotations revealed that animals receiving pieces of VM tissue or dissociated cells showed significant improvement in ipsilateral rotation 4 weeks post transplantation. By 6 weeks post transplantation, animals receiving pieces of VM tissue showed a trend for further improvement, while those receiving dissociated cells remained at their 4 week scores. Postmortem cell counts showed that the number of dopaminergic neurons in dissociated cell transplants was significantly lower than that surviving in transplants of intact tissue. When assessing the correlation between the number of dopamine cells in each transplant, and the improvement in rotation bias in experimental animals, it was shown that transplants of whole pieces of VM tissue offered greater predictability of graft function based on their dopamine cell content. Such results suggest that maintaining the integrity of VM tissue during implantation improves dopamine cell content, and that the dopamine cell content of whole tissue grafts offers a more predictable outcome of graft function in an animal model of Parkinson’s disease.